Software tools for rapid prototype as design - Withell, AJ; Diegel, O; Reay, S (Centre for Rapid and Sustainable Product Development, 2011)
Design teams are expected to produce physical prototypes that demonstrate the working principles of their designs. These projects may involve multiple areas of technology, such as industrial design, electronics, mechanical engineering, software, and even marketing. The integration of physical, threedimensional prototypes into the new product development (NPD) process, i.e. ‘Prototype as Design’ is an effective way to evaluate form, ideas, testing function, and for optimising products for intended users. The advent of the latest additive manufacturing and CAD/CAM technologies has transformed this process into a ‘Rapid Prototype as Design’ (RPaD) methodology. This paper describes the RPaD methodology and presents a case study of student product design projects, in which RPaD was used as a key design methodology. It also presents a software ‘toolbox’ that is used as a tool to facilitate the process, and use of the toolbox is demonstrated in the case studies.